A review of antioxidant in paddy ( Oryzae Sativa ) / Fara Syahidha Markum - Markum, Fara Syahidha (Faculty of Plantation and Agrotechnology, 2017)
Serious disease such as cancer have become a greater concern nowadays that are causing by free radical. This concern was lead to a study on the antioxidant that derived from the rice as an alternative to reduce the chance to get the disease. Paddy or Oryzae Sativa origin from plantae known as Asian rice. Paddy rich with antioxidant molecule such as phenolic acid, tocopherol, flavanoid, anthocyanin and y-oryzanol. Paddy also contains a radical which is lead to the emergence. This can be overcome by using hydroxyl radical that helps antioxidant molecule in reducing the free radical formation and it is occur naturally. This study is to investigate and evaluate the antioxidant activities in 16 types of rice from Malaysia, Thailand and Indonesia. This evaluation are use ABTS decoloration, FRAP radical scavenging, DPPH radical scavenging and TPC of ethanolic solution. The rate of antioxidant also affected by several factors such as salinity stress which effect the time taken for yield production. This review are indicate that activity of antioxidant molecules is high for all types of rice.